Strategies for measuring long-term control in atopic dermatitis trials: a systematic review - Barbarot, Sebastien; Rogers, Natasha K.; Abuabara, Katrina; Aubert, Helene; Chalmers, Joanne; Flohr, Carsten; Hanfin, Jon; Naldi, Luigi; Margolis, David J.; Paul, Carle; Ridd, Matthew J.; Schuttelaar, Marie-Louise Anna; et al. (Elsevier, 2016)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin disease. There are no standardised methods for capturing long-term control of AD.